2018 14th International Wireless Communications &Amp; Mobile Computing Conference (IWCMC) 2018
DOI: 10.1109/iwcmc.2018.8450458
|View full text |Cite
|
Sign up to set email alerts
|

Practical Compressed Sensing and Network Coding for Intelligent Distributed Communication Networks

Abstract: Based on the impressive features that network coding and compressed sensing paradigms have separately brought, the idea of bringing them together in practice will result in major improvements and influence in the upcoming 5G networks. In this context, this paper aims to evaluate the effectiveness of these key techniques in a cluster-based wireless sensor network, in the presence of temporal and spatial correlations. Our goal is to achieve better compression gains by scaling down the total payload carried by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Consequently, in the future, we plan the in‐depth study of this algorithm and will propose modifications that would suit both techniques to meet with the current 5G network requirements, mainly, the lower delays. On the other hand, we showed that joining compressed sensing and network coding for cluster‐based WSNs could result in significant losses due to the recombinations at cluster heads when one increases the number of hops 37 . We expect that these losses could be rectified if we operate both network coding and compressed sensing in the finite fields, especially in scenarios where the scalability of the framework is indispensable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, in the future, we plan the in‐depth study of this algorithm and will propose modifications that would suit both techniques to meet with the current 5G network requirements, mainly, the lower delays. On the other hand, we showed that joining compressed sensing and network coding for cluster‐based WSNs could result in significant losses due to the recombinations at cluster heads when one increases the number of hops 37 . We expect that these losses could be rectified if we operate both network coding and compressed sensing in the finite fields, especially in scenarios where the scalability of the framework is indispensable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Compressive Network Coding is a joint source and network coding method for approximate data gathering 36 . Finally, the JOint COMpressed sensing and network COding ( JoComCo ) for cluster‐based topologies in WSNs was proposed in 2018 37 . It exploits the temporal and spatial correlations as well as the intercorrelation and intracorrelation among the sensors belonging to different clusters.…”
Section: State‐of‐the‐art and Agnostic Combinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the idea of AoI stems from time redundancy of data, implying that multiple close updates congest the processing at the end server without significantly enhancing the information freshness, and it may be convenient to evenly spread them over time. We are extending this concept to spatial redundancy, where some updates can be avoided if another source has already sent an update about a process that correlates with the one of interest or is even the same [22].…”
Section: System Modelmentioning
confidence: 99%